Instrumentos de avaliação: mecanismos de gestão na UTFPR - Pirolla, Cleonice Mendonça (2013)
Currently the technology topics, sustainability, productivity and innovation have gained attention in the strategy of organizations, particularly in more dynamic productive environments of society. It is noticed that, often, these environments have neglected the most important variable of an enterprise, people. It is forgotten that transformations are the result of individual competencies, skills, motivation and engagement of the same towards institutional projects. In pursuit of continuous improvement, several mechanisms are used as a source of research and subsidies for process reorientation, changes of behavior and management planning. This dissertation raised up the evaluation tools of a public institution and verified if the same served as a resource for management improvement. The methodology was based on desk research and case study. The data collection occurred through electronic poll and the evaluation tools surveyed were: Organizational Climate Survey, Employee Assessment, Management Assessment, Teacher Evaluation by Student and External Assessment.